Analisis Kesalahan Kalimat Bahasa Indonesia pada Teks Pidato Siswa MTs.Ma’arif 16 Nurul Hidayah Banyubang Solokuro Lamongan - Busyro Busyro (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2020)
The main purpose of this study was to explain the error to the wrong use of sentences in the writing of speech tech students MTs Ma'arif 16 Nurul Hidayah Banyubang Solokuro Lamongan. Describes several aspects of frequent errors, and the factors that cause errors. This research was designed using a descriptive qualitative research method. This research sample is a text written by students as a speech material extra-curricular at MTs. Ma'rif 16 Nurul Hidayah Solokuro Lamongan. Sampling techniques used in this research are data collection, data reduction, data presentation, and verification. The results of this study can be concluded that: the first one that experienced a frequent language error in the text of the speech of student of MTs.Ma'arif 16 Nurul Hidayah Banyubang Solokuro Lamongan is a linguistic element that occurred in four categories of errors, namely: spelling errors; word formation, syntactic aspects, and semantic aspects. Second, the use of punctuation.